PERANCANGAN GAME EDUKASI DESCRIPTIVE TEXT BERBASIS MOBILE DI SMP MUHAMMADIYAH 1 GATAK - Ressa Melasovic; Siti Supeni; Yudhistiro Pandu Widoyoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The objectives of this research are: 1) To determine the design of a mobile-based educational game for Descriptive text material at SMP Muhammadiyah 1 Gatak; 2) To determine the feasibility of the designed mobile-based educational game to be used as a learning medium in English language subjects for Descriptive text material at SMP Muhammadiyah 1 Gatak. This research was conducted at SMP Muhammadiyah 1 Gatak. This study uses the Research and Development method with the ADDIE development model. Data collection used observation, interviews, questionnaires, and documentation, and also employed the Blackbox Testing system and feasibility validation by experts, as well as student response results to provide feedback regarding the feasibility of the learning medium. Product feasibility validation was analyzed and converted using a Likert Scale to determine the percentage score for the feasibility of the "JUNGLE DASH" educational game learning medium and passed the blackbox testing. The results of this study are: (1) producing an educational game-based learning media product called "JUNGLE DASH" which functions to assist students as a learning medium and to help teachers in delivering material through educational game-based learning media as a means to increase student enthusiasm for learning at SMP Muhammadiyah 1 Gatak. Based on the results of the Blackbox Testing conducted, the learning media can be operated properly; (2) The "JUNGLE DASH" Educational Game obtained an average feasibility percentage score of 86% in the highly feasible category from media experts, an average feasibility percentage score of 94% in the highly feasible category from material experts, and an average feasibility percentage score of 89% in the "highly feasible" category from the teaching teacher.